The Influence of Molecular Weight Hydroxypropylcellulose on Rheological Properties of Aqua-Ethanol-Coal Suspensions - Dymytriuk, T.M.; Savitskyi, D.P.; Makarov, A.S. (Physics and Chemistry of Solid State, 2015)
The rheological properties of aqua-ethanol-coal of varying degrees coal metamorphism, stabilized by macromolecular surfactants was studied by rotational viscometry. It was found that including of hydroxypropylcellulose as a stabilizer for dispersions of coal and water-ethanol mixtures, increasing their stability. It is shown that with increasing molecular weight of hydroxypropylcellulose viscosity of disperse systems increases, regardless of the degree of coal metamorphism. With increasing concentrations of the polymer injected more than 0.01 % of coal the viscosity of the systems increases sharply.